2002
DOI: 10.1038/sj.ijo.0802053
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle triglycerides lowering is associated with net improvement of insulin sensitivity, TNF-α reduction and GLUT4 expression enhancement

Abstract: AIMS=HYPOTHESIS:The aim of the present study was to investigate the relationship between intramyocytic triglycerides levels, muscle TNF-a and GLUT4 expression and insulin resistance. METHODS: Insulin sensitivity was studied in 14 severely obese women (BMI > 40 kg=m 2 ), before and 6 months after low-dietary intake or bariatric malabsorptive surgery (bilio-pancreatic diversion, BPD), by the euglycaemic hyperinsulinaemic clamp technique, while the amount of intramyocytic triglycerides was chemically measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 38 publications
(31 reference statements)
5
45
0
1
Order By: Relevance
“…The large increase in MFN2 mRNA levels was associated with the net improvement of insulin-dependent whole-body glucose We have previously demonstrated that insulin resistance in morbidly obese patients is positively associated with the IMTG content and with TNF-α expression and inversely correlated to SLC2A4 expression [16]. In agreement with this previous observation [16], whole-body glucose uptake was found to be a linear function of SLC2A4 expression in skeletal muscle.…”
Section: Discussionsupporting
confidence: 85%
“…The large increase in MFN2 mRNA levels was associated with the net improvement of insulin-dependent whole-body glucose We have previously demonstrated that insulin resistance in morbidly obese patients is positively associated with the IMTG content and with TNF-α expression and inversely correlated to SLC2A4 expression [16]. In agreement with this previous observation [16], whole-body glucose uptake was found to be a linear function of SLC2A4 expression in skeletal muscle.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous study skeletal muscle TNF-α mRNA levels and fasting plasma insulin were reduced after malabsorptive surgery causing substantial weight loss (~26 kg) in severely obese women (BMI >40 kg/m 2 ) [8]. In this previous study, GLUT4 mRNA levels were elevated, correlating inversely with the reduction in skeletal muscle TNF-α mRNA.…”
Section: Dietary Interventionmentioning
confidence: 52%
“…Skeletal muscle, however, is less well studied. Recently it was shown that massive weight loss through malabsorptive surgery can reduce TNF-α mRNA levels in skeletal muscle [8]. In the same study, the more moderate weight loss associated with energy restriction had no effect.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations